(3TbGFb GdCJQL aj QbGFb GdZfLs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3gPG LRA jSei HTbGFb GdCJQL ai QbGFb GdZfL , CdaJg LhGHkG dSGFd Yf Mceg TQYkG hChQOJ ajg ef GdahGFO eGdGjRjO Ydjg LeYkG ,hCNJQJ dg gPG GdGSe deG JVefg ef dWGFa GdHOjY UfYkG s
(3BNQgG (B:s
(3hCfTO ai GdMeGSI dQLd jgLh CeQCJg (B: (3MOjK cbdY GdVQS Ch fJa TGQH hZfL cYXe GdCfa Yjd Hg UHQi hJaJQ Yf adL YOeJ MOjKgG hYf LHdi Wi hYf gQei eUQ s
(3fSNI KGfjIs
(3YdjgG Jedc HJGQjN (B1173(3g`s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B128 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B534s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B143 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs